Analyses of Plastome Sequences Improve Phylogenetic Resolution and Provide New Insight Into the Evolutionary History of Asian Sonerileae/Dissochaeteae - Zhou, Qiujie; Lin, Che-Wei; Ng, Wei Lun; Dai, Jinhong; Denda, Tetsuo; Zhou, Renchao; Liu, Ying (Frontiers in Plant Science, 2019)
Sonerileae/Dissochaeteae (Melastomataceae) comprises ca. 50 genera, two thirds of which occur in Southeast Asia. Phylogenetic relationships within this clade remain largely unclear, which hampers our understanding of its origin, evolution and biogeography. Here, we explored the use of chloroplast genomes in phylogenetic reconstruction of Sonerileae/Dissochaeteae, by sampling 138 species and 23 genera in this clade. A total of 151 complete plastid genomes were assembled for this study. Plastid genomic data provided better support for the backbone of the Sonerileae/Dissochaeteae phylogeny, and also for relationships among most closely related species, but failed to resolve the short internodes likely resulted from rapid radiation. Trees inferred from plastid genome and nrITS sequences were largely congruent regarding the major lineages of Sonerileae/Dissochaeteae. The present analyses recovered 15 major lineages well recognized in both nrITS and plastid phylogeny. Molecular dating and biogeographical analyses indicated a South American origin for Sonerileae/Dissochaeteae during late Eocene (stem age: 34.78 Mya). Two dispersal events from South America to the Old World were detected in late Eocene (33.96 Mya) and Mid Oligocene (28.33 Mya) respectively. The core Asian clade began to diversify around early Miocene in Indo-Burma and dispersed subsequently to Malesia and Sino-Japanese regions, possibly promoted by global temperature changes and East Asian monsoon activity. Our analyses supported previous hypothesis that Medinilla reached Madagascar by transoceanic dispersal in Miocene. In addition, generic limits of some genera concerned were discussed.